Synthesis of lithium fluoride from spent lithium ion batteries - Suarez, Daniela Silvana (2017)
Lithium (Li) is considered a strategic element whose use has significantly expanded. Its current high demand is due to its use in lithium ion batteries for portable electronic devices, whose manufacture and market are extensively growing every day. These days there is a great concern about the final disposal of these batteries. Therefore, the possibility of developing new methodologies to recycle their components is of great importance, both commercially and environmentally. This paper presents results regarding important operational variables for the dissolution of the lithium and cobalt mixed-oxide (LiCoO2) cathodes from spent lithium ion batteries (LIBs) with hydrofluoric acid. The recovery and synthesis of Co and Li compounds were also investigated. The dissolution parameters studied were: temperature, reaction time, solid-liquid ratio, stirring speed, and concentration of HF. The investigated recovery parameters included: pH, temperature, and time with and without stirring. The final precipitation of lithium fluoride was also examined. The results indicate that an increase in the HF concentration, temperature, and reaction time favors the leaching reaction of the LiCoO2. Dissolutions were close to 60%, at 75ºC and 120 min with a HF concentration of 25% (v/v). The recovery of Co and Li were 98% and 80%, respectively, with purities higher than 94%. Co and Li compounds, such as Co3O4 and LiF, were synthesized. Furthermore, it was possible to almost completely eliminate the F- ions as CaF2.